A new species of the genus Riccardoella (Acari: Prostigmata: Ereynetidae) from the land snail Tauphaedusa tau (Gastropoda: Clausliidae) in Japan - Waki, Tsukasa; Hiruta, Shimpei F; Shimano, Satoshi (Zootaxa, 2018)
A new mite species, Riccardoella (Proriccardoella) tokyoensis n. sp., is described from the lungs of the terrestrial gastropod Tauphaedusa tau (Boettger, 1877) (Clausliidae) collected in a forest city park of Tokyo, Japan. The new species is distinguished from other Riccardoella species by the following morphological characters: tibia II bears 2 setae (vs. 3 setae in other species); femur I bears 5 setae (vs. 4 or 6 setae in other species); seta of trochanter I is absent (vs. 1 seta in other species). Our phylogenetic tree based on amino acid sequences of the mitochondrial cytochrome c oxidase subunit 1 (COX1) confirmed that another member of the family Ereynetidae, “Ereynetidae sp.”, is the closest relative with 85% sequence identity.